WILL ACCOUNTING STUDENTS CHOOSE A CAREER AS A PUBLIC ACCOUNTING? A CASE STUDY OUTCOME BY A META-ANALYSES - Handayati, Puji (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 8 No 1 (2022): The 8th International Conference Of Islamic Economics And Business (ICONIES 2022), 2022)
The purpose of this study was to analyze and identify the results of previous studies related to career choice factors by accounting students. Meta-analysis method was used out of 87 scientific articles during 2005-2019 where 14 articles were designated as research samples. Factors of family and closest people, financial rewards, and job opportunities are considered as independent variables, and in contrast, career choice to become a public accountant are considered as dependent variables in this study. The results showed that family and closest people factors, financial rewards and job opportunities had a significant positive effect on career choice for accounting students. The outcomes obtained in this study will be useful for other researchers to identify the relationship between the factors of family and closest people, financial rewards, job opportunities, and career choice for future research.